LTCC and Thick-film Ceramic Magnetic Sensors for Tokamak Nuclear Fusion. (2016) - Maeder, Thomas; Jacq, Caroline; Testa, Duccio; Toussaint, Matthieu; Stöck, Martin; Corne, Adrien; Güniat, Lucas; Ellenrieder, Benoît; Jiang, Xinyue; Windischhofer, Philipp; Schlatter, Christian; Ryser, Peter
Abstract: The present contribution gives an overview of our work on non-conventional magnetic coil sensors for diagnostics and plasma stability control of nuclear fusion experiments in tokamaks. Instead of wire wound around a core, these devices consist of printed conductor wire coils on ceramic substrates, and are based on LTCC (low-temperature co-fired ceramic) and thick-film technology, which allow creation of monolithic multilayer coils with excellent stability. For 3D sensing, an innovative modular design combining LTCC coils and an alumina base has been developed. Finally, the important aspects of integration, manufacturing, mounting and interconnection are discussed.